Analisis Fungsi Biaya Industri Manufaktur Besar Dan Sedang Kota Surakarta - Riyardi, Agung; Sakti, Vidi Pramady; Jatmiko, Candra Tri (Media Mahardhika, 2018)
The goals of this research are specifying a model of a cost minimization based on the indirect cost function and forming an average and marginal cost functions so that factors influence cost and cost structure of Surakarta Industry can be analyzed. The method is a 2010-2015 panel data regression function of the Surakarta Industry. The functional form is the Cobb-Douglas function. The result shows that the best panel model is the intercept varies over time model. This model shows the indirect cost function and cost minimization of the Surakarta Industry. Significant independent variables are the intercept, the number of production, the price of fuel, and the price of raw material. The sign of the intercept is negative. Wage is used to hold the homogenuous in the input price assumption of the cost function. The result also shows that the average and marginal cost functions are  formed. Entering the minimum and maximum values of the number of the production into the functions, it is found that the marginal cost is more expensive than the average cost indicating the average cost of the Surakarta Industry tends to increase. Also, it is found that the average cost of the first group that consists of food, textile, textile product and other industries is the cheapest average cost. The average costs of the second group that consist of paper and printing and chemistry industries is a becoming expensive average cost. The third group is the furniture and rubber industries that is the expensive average cost group.